KARAKTERISTIK DAN TINGKAT STRES SISWI DENGAN KEJADIAN DISMENORE PRIMER DI SMP N 3 SRAGI PEKALONGAN - Riski Yunitasari; Sri Rejeki; Nikmatul Khayati (Universitas Muhammadiyah Semarang, 2017)
Dysmenorrhea is a physical disorder in woman who complained during menstruation, with charateristics of pain before and during menstruation.Dysmenorrhea occurs due to physical distruption such as narrowing of bloodvessels, decreased body condition, and dysmenorrhea caused by psychologicaldisorder such as stress and shock. The Purpose of this study to determine therelationship between the characteristics and stress levels of female students withthe incidence of primary dysmenorrhea in state Junior High School 3SragiPekalongan, used analytic survey with cross sectional approach, conductedon March 24 until 24 Mei, sampling technique used is total sampling, and the totalnumber of samples are 61 respondents. There was no correlation between agecharacteristic, menarche age and the inciden of primary dysmenorrhea. Thishappens because the majority of respondents are 14 years old and the majority of menarche age is 12 years old, while the affecting age is 15-25. There is relationbetween stress level of student with primary dysmenorrhea incidence in stateJunior High School 3 SragiPekalongan, with value of Pvalue=0,006 (P>0.05). Itoccurs because many experience moderate stress was 89 %, caused the work ofendocrine system is disrupted by the increases of the hormone adrenalin whichcauses the uterine muscle tense and causes menstrual pain, then increases thehormone estrogen causes contraction of the uterus. Recommendation from theresearch for further researcher developed by qualitative metodh with deepinterview about factors influencing stress incident at dysmenorrhea. Keywords : Dysmenorrhea, Characteristics, Stress